LITERATUR REVIEW: PENGARUH PEMBERIAN ASI PADA IBU POSTPARTUM DENGAN KEJADIAN POSTPARTUM DEPRESSION - Hanifatur Rosyidah; Ainaya Hafizatul Adibiyah (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Postpartum depression is the situation of depression experienced by mothers after giving birth. Postpartum depression affects the reduction or cessation of the process of breastfeeding to mothers. The purpose of this study was to analyze the effect of breastfeeding mothers with the incidence of postpartum depression on postpartum mothers. The research method was carried out by a literature review study approach using several journal sources that were selected based on predetermined criteria. The data source is based on updated journals with limited journal publication from 2015-2021. The results were showed the differences in the level of depression in postpartum mothers are due to differences in responses or coping mechanisms possessed by each mother. The conclusion is the risks of postpartum depression were occured due to three factors, which are problems with breastfeeding, husband's support, and income.